The data myth: interrogating the evidence base for evidence-based peacebuilding - Roger Mac Ginty; Pamina Firchow (Data & Policy)
This article interrogates three claims made in relation to the use of data in relation to peace. That more data, faster data, and impartial data will lead to better policy and practice outcomes. Taken together, this data myth relies on a lack of curiosity about the provenance of data and the infrastructure that produces it and asserts its legitimacy. Our discussion is concerned with issues of power, inclusion, and exclusion, and particularly how knowledge hierarchies attend to the collection and use of data in relation to conflict-affected contexts. We therefore question the axiomatic nature of these data myth claims and argue that the structure and dynamics of peacebuilding actors perpetuate the myth. We advocate a fuller reflection of the data wave that has overtaken us and echo calls for an ethics of numbers. In other words, this article is concerned with the evidence base for evidence-based peacebuilding. Mindful of the policy implications of our concerns, the article puts forward five tenets of good practice in relation to data and the peacebuilding sector. The concluding discussion further considers the policy implications of the data myth in relation to peace, and particularly, the consequences of casting peace and conflict as technical issues that can be “solved” without recourse to human and political factors.